The new campaign finance sourcebook - Corrado, Anthony, 1957- (Washington, D.C. : Brookings Institution Press, 2005)
"Comprehensive exposition of federal campaign finance law and administration following the enactment, consitutional defense, and implementation of the 2002 Bipartisan Campaign Finance Reform Act (McCain-Feingold)"--Provided by publisher
Introduction / Thomas E. Mann and Anthony Corrado -- Money and politics : a history of federal campaign finance law / Anthony Corrado -- The current state of campaign finance law / Trevor Potter -- The First Amendment and the limits of campaign finance reform / Daniel R. Ortiz -- Campaign finance disclosure laws / Trevor Potter -- Party finances / Anthony Corrado -- Public funding of presidential campaigns / Anthony Corrado -- Speech governed by federal election laws / Trevor Potter and Kirk L. Jowers -- The FEC : administering and enforcing campaign finance laws / Thomas E. Mann -- Election law and the internet / Trevor Potter and Kirk L. Jowers -- Reform agenda / Thomas E. Mann.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Campaign funds -- United States; Campaign funds -- Law and legislation -- United States; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Political Process -- Elections; Campaign funds; Campaign funds -- Law and legislation; United States; Wahlkampffinanzierung; USA; Campaign funds -- United States; Campaign funds -- Law and legislation -- United States; Aufsatzsammlung